Post-traumatic superolateral temporo-mandibular dislocation with intact condyle: case series and literature review - Zegbeh N'guessan Eric Kouassi; Djémi Ernest Martial; Bérété Pornan Issa Jules; Salami Tahib Arnaud; Yapo Assi Romaric Evrard; Illi Biévianda Vincent; Crezoit Grébéret Emmanuel (EDP Sciences, 2022)
Introduction: Supero-lateral temporomandibular dislocations with intact condyles are very rare, particularly in countries of sub-Saharan Africa where they are poorly documented. Materials and method: This was a retrospective study that included all patients received for superolateral temporomandibular dislocation with intact condyle following a maxillofacial trauma. The period covered by the study was from January 2011 to July 2021. Results: 3 patients were studied. According the classification of temporomandibular superolateral dislocation with intact condyle, the first patient had a Type II A, the second and the third patient, type II B. The manual reduction of the first patient luxation was unstable requiring an osteosynthesis of mandibular symphysis to stabilise the reduction of the temporomandibular dislocation. The second patient manual reduction was unsuccessful requiring an open reduction by preauricular approach. The third left against medical advice. Discussion: The occurrence of temporomandibular superolateral dislocation with intact condyle in an underdeveloped city like Bouaké, is not related to the density of road traffic but to the indiscipline of the many motorcyclists who do not wear helmets. Early reduction of the dislocation, early mobilisation of the joint and mechanotherapy positively influence the postoperative outcome.